Um modelo fuzzy-gta-dematel para a avaliação integrada do nível de implementação da produção enxuta - Alcantara , Paulo Guilherme de França (2017)
Lean Production (LP) could be defined as an integrated sociotechnical system with a multidimensional approach that includes management principles and practices, whose main objective is to reduce costs by eliminating waste. The success of LP in Japan and Western has led many organizations to try to implement it. However, some factors led to the failure of its implementation in many companies. When analyzing these factors, it was verified that these companies disregarded two facts: the existence of guiding principles for execution of lean practices and the continuous and synergistic interaction among such practices. Given this context, it was necessary to propose a model that would evaluate, in an integrated way, the level of LP implementation in companies. Thereunto, it was carried out a review about the articles concern LP assessment considering lean practices, in order to understand how evaluations were done, and which quantitative tools were used and, based on this perception, list the needed requirements to develop the model. Thereafter, this study proposed a fuzzy-GTA-DEMATEL reference model for LP assessment. It was composed of 4 factors and 20 sub-factors used in literature. In order to test its applicability, a case study was carried out at an organisation from automotive sector to evaluate the productive process, as well as applying Delphi with 7 LP specialists to evaluate the interactions between the elements. The model showed that studied company presented a high level of LP implementation. Nevertheless, it also pointed out that the company could make improvements in Process management (PM) factor to leverage the LP in its process, specifically in the sub-factors Standardized operations (S21) and Multifunctional workers (S22). Therefore, it was concluded that referential model is relevant and appropriate to assess the level of LP implementation in addition to identifying priorities for improvement. The model also contributed to diagnosis of the current LM stage in a company, in addition to identifying improvement priorities. Finally, the structure of model is considered a contribution, since the adopting company can use its own factors and sub-factors with same effectiveness.